PENGARUH TERPAAN PROMOSI PENJUALAN DAN KUALITAS ULASAN ONLINE KONSUMEN DI MEDIA SOSIAL DENGAN MINAT BELI SEPEDA MOTOR YAMAHA NMAX - Arma Ngabeti; Djoko Setyabudi; Joyo Nur Suryanto Gono (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
Nmax motorcycles as one of Yamaha's products experienced a decline in sales for three consecutive years. Ideally, by issuing sales promotions every year in the form of discounts, cashback, giving vouchers and bonuses should be able to encourage the purchase of motorcycles. On the other hand, there are also online reviews on social media from Nmax users, where Yamaha Nmax gets a high rating with a score of 4.8 out of 5. Reviews that contain positive information should be able to positively grow the buying interest of potential consumers. The study aims to determine the influence of sales promotion and the quality of consumers' online reviews on social media with interest in buying Yamaha Nmax motorcycles.Research is a type of explanatory research using non-probability sampling techniques. The number of respondents was 100 people with male and female criteria, aged 22-34 years, domiciled in Central Java and the Special Region of Yogyakarta, had seen, heard or read online reviews or Yamaha Nmax sales promotions. Testing using a simple linear regression analysis, the results showed that sales promotion affected the buying interest of Nmax motorcycles with a significance value of 0.036 (<0.05). Then, the quality of consumers' online reviews on social media is also confused with the interest in buying Nmax motorcycles with a significance value of 0.007 (<0.01).